PTHE APPLICATION OF THE PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE LEARNING OUTCOMES AND STUDENT ENGAGEMENT IN SCIENCE EDUCATION ON THE TOPIC OF TIME MEASUREMENT FOR FOURTH-GRADE STUDENTS AT SD NEGERI 21 BENGKULU TENGAH - Gorela Sudirman Tono; Barep Hapit Surya Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low learning outcomes and activeness of fourth-grade students in Science and Social Studies (IPAS) learning on the topic of time measurement at SD Negeri 21 Bengkulu Tengah. Based on the pre-cycle test results, only 8 of 27 students (30%) achieved the Learning Objective Achievement Criteria (KKTP), with a class average score of 65.78 and a student activeness level of only 45%. This condition was caused by teacher-centered instruction, a lack of problem-solving activities, and minimal active student engagement. This study aimed to improve student learning outcomes and activeness through the implementation of the Problem Based Learning (PBL) model. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, action, observation, and reflection. The research subjects were 27 fourth-grade students, comprising 11 boys and 16 girls. Data were collected through learning achievement tests, student activeness observation sheets, documentation, and field notes, then analyzed descriptively using quantitative and qualitative approaches. The results showed that the average learning outcome score increased from 65.78 in the pre-cycle to 72.44 in Cycle I and 87.96 in Cycle II, while the percentage of learning mastery increased from 30% to 63% in Cycle I and 93% in Cycle II. Student activeness also increased from 45% in the pre-cycle to 70% in Cycle I and 88% in Cycle II. It can be concluded that the application of the Problem Based Learning (PBL) model effectively improved the learning outcomes and activeness of fourth-grade students in IPAS learning on time measurement material at SD Negeri 21 Bengkulu Tengah.